Jack in the box: inguinal endometriosis. (31st March 2015) - Pandey, Deeksha; Coondoo, Ambika; Shetty, Jyothi; Mathew, Stanley
Abstract : A 39-year-old woman with a left-sided inguinal swelling was referred to us with a diagnosis of inguinal hernia. On asking leading questions, the patient gave a typical history of cyclical pain and increased swelling during menstruation. Fine-needle aspiration biopsy revealed endometrial glands. Preoperatively, the extent of the endometriotic lesion was delineated using MRI. The lesion was approached through the patient's caesarean scar for cosmetic reasons and excised in toto. Final diagnosis was round ligament endometriosis. The patient was asymptomatic at 3, 6 and 12 months' follow-up. This case re-emphasises the fact that endometriosis is an enigmatic disease and can be found anywhere in the body. Thus, a woman of reproductive age presenting with any cyclical symptom should be asked about its relation to her menstrual cycle.